The relationship between nutritional status and the severity of pneumonia in children aged 1-5 - Cut clara Zahira; Nina Herlina; Deviani Utami; Astri Pinilih (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Pneumonia is one of the leading causes of morbidity and mortality among children under five years of age. Nutritional status is known to play an important role in the immune system and may influence the severity of pneumonia. Purpose: To determine the relationship between nutritional status and the severity of pneumonia in children aged 1-5 years. Method: this study used an analytic observational method with a cross-sectional design. The sample consisted of 73 children selected using purposive sampling based on medical record data. Data were analyzed using the chi-square test. Results: the results showed that most respondents were classified as wasted, accounting for 28 children (38.4%), followed by normal nutritional status in 25 children (34.2%) and severely wasted in 14 children (19.2%). In addition, a small proportion of respondents were classified as having a possible risk of overweight and overweight, each accounting for 3 children (4.1%), while no respondents were classified as obese (0%). The majority of respondents experienced severe pneumonia, accounting for 56 children (76.7%). Statistical analysis showed a significant relationship between nutritional status and the severity of pneumonia (p = 0.034; p < 0.05). Conclusion: there is a significant relationship